Cultural values and career goals of the millennial generation: an integrated conceptual framework - Ismail, Maimunah; Hoo, Shien Lu (Journal of International Management Studies, 2014)
This paper aims to develop a conceptual framework of the influence of cultural values on career goals of Millennial generation in Malaysian workforce. The millennial generation refers to individuals who were born in 1980 to 1995. This study is based on reviews of past researches on career goals of employees specifically the millennial generation. To conduct the literature reviews, several keywords were identified. Several electronic databases available at the university’s library such as Proquest, SAGE, Emerald, EBSCOHost, Springer, Science Direct, Soci al Science Citation Index, and Blackwell Synergy were used to search for supporting materials and resources. In the reviews, the authors adopted six dimension of Hofstede’s cultural values namely, power distance, individualism versus collectivism, masculinity versus femininity, uncertainty avoidance, long-term versus short term orientation, and indulgence versus restraint, and their influence on career goals of the millennial generation. This paper yields an integrated conceptual framework that outlines the predictive potential of the six cultural values in explaining career goals of the Millennial generation in the country’s workforce, hence would suggest practical interventions for HRD professionals in managing the dynamic younger workforce from the perspective of career development.